Romantic modernism : nostalgia in the world of conservation - Denslagen, W. F. (Amsterdam University Press, 2009)
Is it possible for conservationists to approve of the reconstruction of old façades when virtually everything behind them is modern? Should they continue to protect the front façade, when the rest of the historic building has vanished? Is it socially responsible to spend government money on reconstructing a historic building that has been completely destroyed? Can one do such a thing fifty years on?. According to reigning ideas in the world of conservation, the answer to all these questions is 'no'. It is felt that building a stage set is dishonest, and rebuilding something that no longer exis.